The impacts and building deficiencies relating to maintenance considerations at design stage / Aljuffry Mohd Ariffin - Mohd Ariffin, Aljuffry (Faculty of Architecture, Planning and Surveying, 2008)
The awareness of having maintenance considerations during design has often neglected by the construction personnel at every stage. This situation has contributed many negative effects towards the completion, and also to the building itself. The research will focus on what are the maintenance considerations during design and also the impacts towards the building. Building owners are beginning to accept that it is not in their best interest to carry out maintenance in a purely manner, but that it should be planned and managed as efficiently as any other corporate activity. This has placed new demands on building owners, requiring them to adopt a more systematic approach of their work. This is where the concept of design for ease of maintenance comes in. This research also reviews on the issues of design maintenance factors in design aspects and proposes factors for designers to take into account during design stage.